Profile of mood and associated factors among participants of a program of cardiopulmonary and metabolic rehabilitation Perfil de humor e fatores associados em participantes de um programa de reabilitação cardiopulmonar e metabólica - Brandt R.* (2012)
Objective: To examine the profile of mood states and associated factors in participants of program of cardiopulmonary and metabolic rehabilitation. Method: One hundred and fortyfour patients answered a characterization questionnaire and the Brunel Mood Scale (BRUMS). The characterization questionnaire consisted of questions about personal and clinical data, and the BRUMS evaluates the mood by six factors: tension, depression, anger, vigor, fatigue and confusion. The data were processed by descriptive statistics and by the Mann-Whitney test and inferential (α = 0,05). Results: In general, patients with heart and metabolic diseases had good mental health, with high levels of vigor associated with low levels of tension, depression, anger, fatigue and confusion. Older participants showed higher levels of tension, anger, fatigue and confusion, while participants who have heart failure showed worse levels of tension and fatigue. Smokers had lower vigor and increased tension, depression and anger. Conclusion: Patients with heart disease participating in a rehabilitation program showed good mental health evaluation. Adults participants, with dyslipidemia, heart failure and smokers have more depressed mood.